P244 The use of anti-malarial therapy in UK Rheumatology practice. A UK-based pilot survey for the BILAG group. (23rd April 2022) - Kaul, Arvind; Mason, Alice; Edwards, Christopher; Vital, Ed
Abstract: Background/Aims: Antimalarials have an important role in the management of autoimmune rheumatic disease, especially lupus (SLE) and other connective tissue diseases (CTD). A large North American study demonstrated a risk of retinopathy with hydroxychloroquine, increasing at doses above 5mg/kg and after 10 years or more of continuous therapy. This has influenced the development of specific monitoring ocular guidance for hydroxychloroquine although there has been less attention to potential side effects in routine use. Our aim was to examine hydroxychloroquine use including the effect of changes in ophthalmology guidance Methods: We designed a 21-question internet-based survey. This requested information on antimalarials including hydroxychloroquine brand, dosing, monitoring and concerns about use. We requested information about alternatives to hydroxychloroquine including mepacrine and chloroquine, barriers to and indications for prescribing these alternative antimalarials. Results: We received 69 responses, 59 (86%) Consultants, 10 (14%) ST's from across the United Kingdom of which 51% worked in a district general hospital (DGH) setting. Of the Consultants, 28 (47%) ran dedicated CTD clinics. Regarding hydroxychloroquine, 39 respondents (57%) used a defined local pathway for Hydroxychloroquine retinopathy screening. While 59/69 (86%) did not know which hydroxychloroquine brand their pharmacy dispensed, of the remainder, 14/19 (74%) used Quinoric. Regarding hydroxychloroquine dosing, 83% targeted weight-based maintenance dosing with most of these (77%) maintaining at the currently recommended 5mg/kg body weight or less, while 23% used 6.5mg/Kg. No participants measured hydroxychloroquine drug levels. Potential ocular toxicity, cardiac arrythmias and skin hyperpigmentation were reported as the most significant concerns with hydroxychloroquine usage. Of the alternatives, mepacrine was never used by 39%, (77% for chloroquine) while only 4% used either often or very often. Barriers to prescription of these alternative antimalarials were most commonly GP or local Pharmacy unavailability (39% and 17 retrospectively). However, mepacrine/ hydroxychloroquine combination was used by 32% of respondents, most often for refractory skin disease (21 respondents), refractory joint disease (five respondents) and as a steroid sparing drug (six respondents). Conclusion: Our results suggest several aspects in which hydroxychloroquine use could be improved. Although recent evidence demonstrates the potential for significant ocular toxicity with Hydroxychloroquine in those taking > 5mg/kg body weight and for >10 years we found practice still varied with 43% Rheumatologists not using a dedicated ocular screening pathway making monitoring long term potentially hazardous. Alternatives to hydroxychloroquine are not considered by 39% perhaps reflecting paucity of data for mepacrine and chloroquine, especially in circumstances including pregnancy but also cost and lack of availability. Our results suggest a need for standardised hydroxychloroquine monitoring processes including improved ophthalmic screening with Optical Coherence Tomography, a need for more evidence about the potential benefits and hazards of hydroxychloroquine and alternative antimalarials and availability of prescribing guidelines. Disclosure: A. Kaul: Consultancies; Dr Kaul has received fees for Advisory Boards for AbbVie, Janssen, Novartis, Lilly. Member of speakers' bureau; r Kaul has received speaker fees from AbbVie, Novartis, Janssen, Leo, Pfizer. A. Mason: None. C. Edwards: None. E. Vital: None.